Inovasi Pembuatan Puding: Meningkatkan Produksi ASI Ibu Nifas Dengan Pemanfaatan Kacang Merah Dan Sari Daun Katuk - Biti, Maria Ratni; Surya, Maria Febriani; Bebhe, Maria Maximiliana; Lourdes, Maria E.; Dasul, Maria S; Purnama, Maria E; Danu, Maria Rosita Elga; Bunga, Maria Meldiana; Yane, Maria S.; Densi, Maria S; Trisnawati, Reineldis E. (Pakis Journal Institute, 2025)
This community service aims to increase breast milk production in breastfeeding mothers through the innovation of making pudding from natural ingredients, namely red beans and katuk leaf extract. Increasing breast milk production is very important for the success of exclusive breastfeeding during the first six months of a baby's life, which supports optimal growth and development of the baby. The approach taken includes counseling and practice of making pudding that combines the high nutritional content of red beans and katuk leaves, which are traditionally known to have the effect of increasing breast milk volume. The sampling technique using pre-test and post-test showed an increase in knowledge and risk of successful breastfeeding in postpartum mothers who participated in this activity. The results showed that this local ingredient-based pudding innovation was effective in helping to increase breast milk production, supporting the sustainability of exclusive breastfeeding, and has the potential to be a natural solution that is easy to apply in the community.